Suara Subaltern Perempuan dalam Puisi Cica 96 karya Chyntia Hariadi: Kajian Feminisme Poskolonial - Jihan Rizki Anisa; Aditya Ansor Alsunah; Lina Siti Nurwahidah; Cecep Dudung Julianto (Asosiasi Ide Bahasa Kepri, 2026)
This study aims to uncover the voices of subaltern Chinese women in Chyntia Hariadi’s poetry collection CICA 96 using Gayatri Spivak’s postcolonial feminist approach. The work captures the experiences of minority women facing historical, social, and political pressures, particularly racial discrimination and the trauma following the 1998 reforms. Chinese women in the poems are depicted as experiencing double oppression in the form of gender and race-based subordination that limits their bodies, identities, and social spaces. The method used is descriptive qualitative, with textual analysis of 17 poems purposively selected based on Spivak’s three main concepts: double oppression, limited representation, and hegemony and ethical politics. The results show that double oppression is evident in the pressures of family culture, racial stereotypes, and social domination that limit the freedom of Chinese women from childhood. Limited representation emerges through the metaphor of silence, state symbols that conceal identity, and silence as a coping strategy when women’s voices are not recognized in the public sphere. Hegemony and ethical politics are reflected in historical trauma, state violence, and collective memory, which shape fragmented identities and persistent insecurity. Overall, CICA 96 provides an alternative space for subaltern women to voice their experiences through symbols and poetic language, thus reintroducing voices that have been suppressed by patriarchy, racism, and state power. This research is expected to enrich feminist literary studies in Indonesia and open up space for further research on minority identities and historical trauma in modern literature.